Pengembangan Media Pembelajaran Interaktif Berbasis Powerpoint Untuk Meningkatkan Pemahaman Bilangan Cacah Siswa Kelas 6 SDN Baratajaya - Fachrezy, Muhammad Riza; Effendi, Bilqis Trihapsari; Sari, Emi Suci Lukita; Salsabillah, Merzynindia Putri; Maulidyanti, Atika; Istiq'faroh, Nurul; Zahroh, Ulfi Aminatuz (CV. Kurnia Grup, 2025)
This study aims to develop PowerPoint-based interactive learning media to enhance the understanding of natural numbers among 6th-grade elementary school students. The research employed the Research and Development (R&D) method using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research subjects were 30 students from VI Elementary School Baratajaya. Data was collected through observations, interviews, questionnaires, and learning outcome tests. Media and material expert validation results showed the learning media was suitable for use with an average score of 86.5%. The implementation of learning media demonstrated improved student understanding with an N-gain value of 0.71 (high category). Student response to the learning media showed a satisfaction rate of 88.3%. It can be concluded that PowerPoint-based interactive learning media effectively improves 6th-grade elementary school students' understanding of natural numbers.